MODEL ADOPSI INOVASI TEKNOLOGI PADA USAHA TANI SEMANGKA DI KECAMATAN MUARA SABAK BARAT KABUPATEN TANJUNG JABUNG TIMUR - Rokhmadiyani, Lily; Suandi, Suandi; Wahyuni, Ira (Agros Journal of Agriculture Science, 2024)
This research aims to determine the description of watermelon farming, to determine the level of adoption of technological innovation in watermelon farming and to analyze what factors influence watermelon farming in Muara Sabak Barat District, East Tanjung Jabung Regency. Analysis uses the SEM-PLS technique. The number of respondents was 92 people, with 7 hypotheses set. The research results show that the watermelon farming being developed focuses on non-seed types of watermelon because it is more profitable. The level of adoption of technological innovation in research locations from superior breeding technology to marketing by the majority of farmers is in the high category. The results of the analysis of the role of extension workers on the level of adoption, the characteristics of innovation, farming, and the level of adoption on farming and the characteristics of innovation on farming have a significant effect. Indirectly, the role of extension workers in farming through the level of adoption has an influence but is not significant.